The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acsnano.5b00672
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Nanomechanical, and Computational Characterization of d,l-Cyclic Peptide Assemblies

Abstract: The rigid geometry and tunable chemistry of D,L-cyclic peptides makes them an intriguing building-block for the rational design of nano-and microscale hierarchically structured materials. Herein, we utilize a combination of electron microscopy, nanomechanical characterization including depth sensing-based bending experiments, and molecular modeling methods to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…Computer simulation studies also aim to predict the molecular organization of peptide molecules and can be used for the optimization of peptide design in conjunction with experimental findings [299][300][301][302][303]. Incorporation of the experimental results and the simulation outputs developed using different molecular dynamics (MD) simulation programs improves the information on the structural properties of the peptide assemblies [93,228,[304][305][306][307]. Previously, successful candidates were determined among 8000 different peptide molecules using computational approaches.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulation studies also aim to predict the molecular organization of peptide molecules and can be used for the optimization of peptide design in conjunction with experimental findings [299][300][301][302][303]. Incorporation of the experimental results and the simulation outputs developed using different molecular dynamics (MD) simulation programs improves the information on the structural properties of the peptide assemblies [93,228,[304][305][306][307]. Previously, successful candidates were determined among 8000 different peptide molecules using computational approaches.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…Nanomechanical properties of the D, L cyclic peptide assemblies were determined via depth sensing-based bending system (top) and the fractures formed on the nanostructures during the measurement were imaging using electron microscopy (bottom). Adapted with permission from [93]. Copyright 2015 American Chemical Society.…”
Section: Supramolecular Self-assembled Peptide Catalystsmentioning
confidence: 99%
“…However, MC stacking is generally too weak to produce nanotubes with the high aspect ratios (>10 3 ) of CNTs and biological filaments. Stacked MCs instead almost always exhibit aspect ratios around 10 as short, individual assemblies or longer structures stabilized by bundling (12)(13)(14), limiting their utility as isolated nanostructures (15). Alternatively, when functionalized with many long alkyl or alkyloxy side chains, they form bulk liquid crystalline phases (16)(17)(18)(19), with assembly sometimes driven by the presence of metal ions or organic guests (20).…”
mentioning
confidence: 99%
“…69 Recent advances in electron microscopy techniques, combined with novel nanomechanical analysis allowed the insightful characterization of the mechanical properties and the aggregation propensity of the Leu substituted peptide. 70 This study revealed that the assembly of this CP, followed by a hierarchical bundling pattern, resulted in the formation of nanotube fibers. This bundling process gave rise to longer (several tens of μm) and thick (up to 1 μm) nanotubular bundles.…”
mentioning
confidence: 81%